2018
DOI: 10.1055/s-0038-1639346
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Dysphagia Lusoria Caused by Right-Aortic Arch with Kommerell Diverticulum: Left Heart Bypass without Subclavian Revascularization

Abstract: The authors present the case of a 26-year-old patient suffering from dysphagia because of compression by a Kommerell diverticulum in right aortic arch anomaly. Open surgical arch and descending aorta replacement with left heart bypass without left subclavian artery reimplantation was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…12 subjects with ARSA Does not present China Not reported Prince et al 1996 [50] Observational study (19) 1 subject with ARSA Does not present USA Not reported ARSA = aberrant right subclavian artery, CI = confidence interval, KD = Kommerell's diverticulum.…”
Section: Does Not Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…12 subjects with ARSA Does not present China Not reported Prince et al 1996 [50] Observational study (19) 1 subject with ARSA Does not present USA Not reported ARSA = aberrant right subclavian artery, CI = confidence interval, KD = Kommerell's diverticulum.…”
Section: Does Not Presentmentioning
confidence: 99%
“…Such is the case of aberrant left subclavian artery, which presented a retroesophageal course pattern compressing the esophagus and generating symptoms that correspond to LD. [14][15][16][17][18][19][20] And even more, the study by Quintero-Pérez et al [21] describes an aberrant right internal carotid artery with a retropharyngeal course pattern, which would generate compression of the pharynx and thereby result in symptoms associated with LD. This evidences the need to clarify the proper use of the term Lusory artery when used to describe the vessel that compresses the esophagus.…”
Section: Introductionmentioning
confidence: 99%
“…Open surgical repair is challenging and requires careful planning. 2 In pediatric patients, the sacrifice of the subclavian artery is a common procedure, however, in older ages it is related to hypotrophy of the affected thoracic limb. Simple ligation of the subclavian artery risks "subclavian-vertebral steal" and may be associated with limb length discrepancy without complete resolution of symptoms.…”
Section: Introductionmentioning
confidence: 99%